Anxiety and depressive symptoms in children and adolescents during COVID-19 pandemic: a transcultural approach - Orgilés, Mireia (2021)
Background: Despite being necessary to delay the spread of COVID- 19, home confinement could have affected the emotional well-being of children and adolescents. Knowing which variables are involved in anxiety and depressive symptoms could help to prevent young people’s psychological problems related to lockdown as early as possible. This crosssectional study aims to examine anxiety and depressive symptomatology in Italian, Spanish, and Portuguese children and adolescents in order to determine which variables are related to poorer well-being during the pandemic. Method: The parents of 515 children, aged 3-18 years old, completed an online survey. Children’s anxiety symptoms were assessed using the Spence Children’s Anxiety Scale-Parent Version, and depressive symptoms were measured with the Short Mood and Feelings Questionnaire-Parent Version. Results: We found differences in anxiety and depression between countries, with higher anxiety scores in Spanish children, and higher depression scores in Spanish and Italian children compared to the Portuguese. Anxiety and depressive symptoms were more likely in children whose parents reported higher levels of stress. Conclusions: These findings are discussed in the light of detecting and supporting affected children as early as possible.